Interstitial lung disease and obstructive sleep apnea. (August 2021) - Khor, Yet H.; Ryerson, Christopher J.; Landry, Shane A.; Howard, Mark E.; Churchward, Thomas J.; Edwards, Bradley A.; Hamilton, Garun S.; Joosten, Simon A.
Summary: Obstructive sleep apnea (OSA) is one of the most common comorbidities in patients with interstitial lung disease (ILD). Growing evidence highlights the significance of sleep disturbance on health outcomes in this population. The relationships between ILD and OSA are complex and possibly bidirectional, with multiple mechanisms postulated for the pathogenic and physiologic links. This review synthesizes current evidence and hypotheses regarding different aspects of the relationships between ILD and OSA, emphasizing the interactions between epidemiology, pathogenesis, and pathophysiology.